Otimização de custos de viagem mediante a redução de velocidade para aproximação de um navio a porto de maré - Angelino Pérez, Tarik Osiris (2017)
Slow steaming in the approach of a ship to a tidal port taking into account tides results in ship fuel consumption and waiting cost reduction and a concomitant decrease in greenhouse gas emissions. In this dissertation, a mathematical optimisation model is developed for the formulation of this problem. The aforesaid model is computationally implemented employing optimisation and computational fluid dynamics program. The model is applied to a hypothetical example and a real life case study based on São Marcos Bay, Maranhão, Brazil.